Putative dioxygen‐binding sites and recognition of tigecycline and minocycline in the tetracycline‐degrading monooxygenase TetX. (25th September 2013) - Volkers, Gesa; Damas, João M.; Palm, Gottfried J.; Panjikar, Santosh; Soares, Cláudio M.; Hinrichs, Winfried
<x xml:space="preserve">Abstract</x> Expression of the aromatic hydroxylase TetX under aerobic conditions confers bacterial resistance against tetracycline antibiotics. Hydroxylation inactivates and degrades tetracyclines, preventing inhibition of the prokaryotic ribosome. X‐ray crystal structure analyses of TetX in complex with the second‐generation and third‐generation tetracyclines minocycline and tigecycline at 2.18 and 2.30 Å resolution, respectively, explain why both clinically potent antibiotics are suitable substrates. Both tetracyclines bind in a large tunnel‐shaped active site in close contact to the cofactor FAD, pre‐oriented for regioselective hydroxylation to 11a‐hydroxytetracyclines. The characteristic bulky 9‐tert‐butylglycylamido substituent of tigecycline is solvent‐exposed and does not interfere with TetX binding. In the TetX–minocycline complex a second binding site for a minocycline dimer is observed close to the active‐site entrance. The pocket is formed by the crystal packing arrangement on the surface of two neighbouring TetX monomers. Crystal structure analysis at 2.73 Å resolution of xenon‐pressurized TetX identified two adjacent Xe‐binding sites. These putative dioxygen‐binding cavities are located in the substrate‐binding domain next to the active site. Molecular‐dynamics simulations were performed in order to characterize dioxygen‐diffusion pathways to FADH2 at the active site.